Microsoft Publisher 2002 - Gaskin, Shelley (Prentice Hall, 2004)
Part of the highly successful Shelly Cashman series, this text offers a clear, step-by-step, screen-by-screen approach to learning basic Microsoft Publisher 2002 skills.